Chlorine oxide gate dielectric material and preparation method and application thereof

By controlling the relative humidity of the reaction chamber and the position of the precursor during the chemical vapor deposition process, the problem of uneven morphology of oxychloride gate dielectric materials was solved, and the growth of oxychloride gate dielectric materials with high dielectric constant and controllable morphology was achieved, thereby improving device performance.

CN120882070APending Publication Date: 2025-10-31SUZHOU INST OF NANO TECH & NANO BIONICS CHINESE ACEDEMY OF SCI
View PDF 0 Cites 2 Cited by

Patent Information

Application Number
CN202511011201.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-07-22
Publication Date
2025-10-31

AI Technical Summary

Technical Problem

In the chemical vapor deposition process of two-dimensional materials, the non-uniform morphology and random shape of oxychloride gate dielectric materials limit device performance and make it difficult to achieve high dielectric constant and stable growth.

Method used

By controlling the relative humidity of the reaction chamber during the chemical vapor deposition process to 8%–20%, and by combining the chemical vapor deposition process with specific positioning of the chloride precursor and substrate material, and by using hygroscopic silica gel to regulate the water vapor concentration, uniform growth of the chloride oxide gate dielectric material is ensured and the morphology is controllable.

Benefits of technology

The high dielectric constant and atomically flat surface of oxychloride gate dielectric material were achieved, which improved the performance of transistor and capacitor devices, exhibiting high dielectric constant, low off-state current, low gate leakage current and high on/off ratio, and effectively avoiding short-channel effect.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN120882070A_ABST
    Figure CN120882070A_ABST
Patent Text Reader

Abstract

The invention relates to an oxychloride gate dielectric material and a preparation method and application thereof. The preparation method comprises the following steps: respectively placing a chloride precursor and a substrate material at the bottom and a single-side opening of a same reaction container with a single-side opening, and placing the reaction container with an opening at one side in a chemical vapor deposition device, with the opening positioned at one side of a vent in the chemical vapor deposition device, regulating the relative humidity of the reaction chamber, and depositing on the surface of the substrate material to obtain the oxychloride gate dielectric material. According to the invention, a chemical vapor deposition preparation process is adopted to control and obtain the oxychloride gate dielectric material with controllable and uniform morphology, so that the problems of random shape and non-uniform morphology of the oxychloride gate dielectric material in the chemical vapor deposition process are solved, the controllable growth of the material is realized, and the material has a high dielectric constant; the material also has an atomic-scale flat surface and is applied to a transistor device and / or a capacitor device, and the device has higher performance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of semiconductor chip technology, and in particular to a chlorine oxide gate dielectric material, its preparation method, and its application. Background Technology

[0002] As integrated circuits continue to pursue higher transistor densities to maintain the exponential growth of Moore's Law, chip manufacturing processes have broken through to the 10-nanometer node, but are gradually approaching the physical limits of silicon-based materials. In advanced processes below 5 nanometers, problems such as short-channel effects, threshold voltage drift, and decreased carrier mobility in silicon-based transistors have worsened significantly, leading to a sharp increase in leakage current and dynamic power consumption, severely limiting the improvement of device performance. To overcome the bottlenecks of traditional semiconductor technology, two-dimensional layered materials, due to their atomic-level thickness, excellent carrier transport characteristics, and intrinsically low power consumption, are considered core candidate materials for integrated circuits in the post-Moore's Law era.

[0003] High-quality, controllable synthesis of two-dimensional materials is a core prerequisite for their transition from basic research to industrial applications. However, due to the lack of dangling bonds on the surface of two-dimensional materials, it is difficult to integrate high-quality, uniform, and high-dielectric-constant gate dielectric layers using standard atomic layer deposition processes. Among numerous preparation methods, chemical vapor deposition (CVD) technology has become the preferred process for the large-scale preparation of graphene, transition metal chalcogenides (TMDs), and emerging two-dimensional dielectric materials due to its excellent material quality, large-area compatibility, and precise layer number control capabilities. Compared to mechanical exfoliation (low yield) and liquid-phase synthesis (high defect density), CVD enables wafer-level growth of single-layer to multi-layer materials through the adhesion and nucleation of gaseous precursor molecules on the substrate surface, with significantly better crystal integrity and interface cleanliness than other routes.

[0004] However, traditional CVD growth processes face challenges such as complex growth kinetics and insufficient morphological uniformity. Especially for highly anisotropic compounds, even minor fluctuations in growth environment parameters can induce crystal plane growth imbalances, leading to problems such as unstable edge structures, uneven thickness, or irregular structures. Small deviations in reaction temperature can disrupt the balance of growth rates across different crystal planes; uneven diffusion of precursor gases can easily cause localized supersaturated crystallization; and atomic-level defects on the substrate surface can induce abnormal nucleation. For chlorine-containing compound systems, the impact of water vapor content is particularly pronounced. While the introduction of water molecules can promote precursor reaction decomposition, excessive water vapor content can trigger negative effects. Therefore, precise control of relative humidity during deposition is crucial for solving the problem of morphological loss of control in chlorine-containing dielectric materials.

[0005] Therefore, how to precisely control the stable growth of the obtained chlorine-containing dielectric material, achieve controllable and uniform morphology, and thus possess high performance is a technical problem that urgently needs to be solved, thereby promoting the development of two-dimensional semiconductor materials in the fields of large-scale device arrays and integrated circuits. Summary of the Invention

[0006] To address the aforementioned technical problems, this invention provides a chloride gate dielectric material, its preparation method, and its applications. This invention employs a chemical vapor deposition (CVD) process to controllably obtain a chloride gate dielectric material with a controllable and uniform morphology, solving the problems of random shape and uneven morphology in chloride gate dielectric materials during CVD. This allows for controllable material growth with a high dielectric constant. Furthermore, it possesses an atomically flat surface, enabling its application in transistor devices and / or capacitor devices, resulting in higher performance.

[0007] To achieve this objective, the present invention adopts the following technical solution:

[0008] In a first aspect, the present invention provides a method for preparing a chloride oxide gate dielectric material, the method comprising the following steps:

[0009] A chloride precursor and a substrate material are placed at the bottom and a single-sided opening of the same reaction vessel. The single-sided opening reaction vessel is placed in a chemical vapor deposition apparatus with its opening facing the vent of the vapor deposition apparatus. A chloride oxide gate dielectric material is deposited on the surface of the substrate material.

[0010] This invention places the chloride precursor at the bottom of a single-sided open reaction vessel and the substrate material at the single-sided opening of the reaction vessel. During the deposition process, the chloride precursor evaporates into molecules and remains inside the reaction vessel, ensuring that the reaction vessel is always filled with a high concentration of precursor gas molecules. This allows for better deposition of high-quality chloride oxide gate dielectric materials on the substrate surface.

[0011] As a preferred technical solution of the present invention, the relative humidity of the reaction chamber is 8% to 20%, for example, 8%, 9%, 10%, 11%, 12%, 13%, 14%, 15%, 16%, 17%, 18%, 19%, or 20%.

[0012] It should be noted that the relative humidity of the reaction chamber in this invention is obtained by instrument measurement and is the ratio between the pressure generated by the current water vapor in the reaction chamber and the pressure generated by the maximum amount of water vapor that the air can hold at the same temperature.

[0013] In this invention, the relative humidity of the reaction chamber is controlled at 8%–20%, and combined with chemical vapor deposition, the controllable growth of oxychloride is achieved. The oxychloride gate dielectric material nanosheets tend to grow into octagonal or quadrilateral shapes, exhibiting more uniform morphology—that is, uniform thickness, consistent size, and high surface flatness—while also possessing a high dielectric constant. When applied to devices, this significantly improves performance. If the relative humidity is too low or too high, the oxychloride gate dielectric material nanosheets will fail to grow properly, resulting in poor morphology, making them unsuitable for various devices and thus unusable.

[0014] As a preferred technical solution of the present invention, the relative humidity in the reaction chamber is achieved by using hygroscopic silica gel, and the method includes:

[0015] The dried silica gel is soaked in deionized water until it is saturated with moisture to obtain hygroscopic silica gel. The hygroscopic silica gel is placed between the vent and the opening of the single-sided open reaction vessel. The hygroscopic silica gel releases water vapor, so that the reaction chamber has relative humidity.

[0016] In this invention, by controlling the amount of moisture-absorbing silica gel added, the pressure of water vapor in the reaction chamber is controlled, allowing different relative humidity levels to exist in the reaction chamber. Furthermore, the moisture-absorbing silica gel of this invention can release water vapor naturally without the need for additional heating treatment.

[0017] It should be noted that the dry silica gel mentioned in this invention refers to a porous adsorbent material with strong water absorption capacity.

[0018] As a preferred embodiment of the present invention, the deposition time is 10 min to 30 min, for example, 10 min, 12 min, 14 min, 16 min, 18 min, 20 min, 22 min, 24 min, 26 min, 28 min or 30 min.

[0019] Preferably, the deposition temperature is 400℃ to 500℃, such as 400℃, 410℃, 420℃, 430℃, 440℃, 450℃, 460℃, 470℃, 480℃, 490℃ or 500℃.

[0020] In this invention, the deposition temperature is controlled at 400℃ to 500℃, which, combined with the deposition time, can regulate the growth and internal structure of the oxychloride gate dielectric material. If the deposition temperature is too low, the nucleation temperature will not be reached, resulting in poor crystallinity of the oxychloride gate dielectric material on the substrate surface; if the deposition temperature is too high, it will damage the internal structure of the oxychloride gate dielectric material, thereby affecting its subsequent performance.

[0021] In this invention, to ensure that the chloride precursor is heated uniformly during chemical vapor deposition, the chloride precursor is placed at the center of the reaction chamber, which also makes the heating temperature closer to the set target temperature, thereby ensuring a better deposition effect.

[0022] As a preferred embodiment of the present invention, the carrier gas provided by the vent includes an argon / hydrogen mixture.

[0023] In this invention, the carrier gas can carry the water vapor released by the hygroscopic silica gel into the reaction vessel, ensuring a better deposition effect.

[0024] Preferably, the air vent provides a carrier airflow rate of 50 sccm to 100 sccm, such as 50 sccm, 55 sccm, 60 sccm, 65 sccm, 70 sccm, 75 sccm, 80 sccm, 85 sccm, 90 sccm, 95 sccm, or 100 sccm.

[0025] As a preferred embodiment of the present invention, the chloride precursor includes any one or a combination of at least two of BiCl3, GdCl3 or VCl3.

[0026] Preferably, the substrate material includes any one of mica substrate, Si substrate, SiO2 substrate or sapphire substrate.

[0027] It should be noted that the present invention does not impose specific requirements or special limitations on the quality of the chloride precursor. Those skilled in the art can adaptively select and adjust the quality of the chloride precursor according to the actual required amount of oxychloride gate dielectric material.

[0028] As a preferred technical solution of the present invention, the preparation method includes the following steps:

[0029] A chloride precursor and a substrate material are placed at the bottom and a single-sided opening of the same reaction vessel. The reaction vessel is placed in a chemical vapor deposition apparatus with its opening facing the vent of the apparatus. Dry silica gel is soaked in deionized water until it becomes saturated with moisture to obtain hygroscopic silica gel. The hygroscopic silica gel is placed between the vent and the opening of the reaction vessel. The hygroscopic silica gel releases water vapor. An argon / hydrogen mixture with a flow rate of 50 sccm to 100 sccm provided by the vent allows the water vapor released by the hygroscopic silica gel to circulate within the reaction vessel, resulting in a relative humidity of 8% to 20% in the reaction chamber. Deposition is performed on the substrate material surface at 400°C to 500°C for 10 to 30 minutes to obtain a chloride oxide gate dielectric material.

[0030] In a second aspect, the present invention also provides a chlorine oxide gate dielectric material, which is prepared according to the preparation method described in the first aspect.

[0031] As a preferred embodiment of the present invention, the chlorine oxide gate dielectric material is a two-dimensional multilayer material.

[0032] In this invention, the chlorine oxide gate dielectric material is a two-dimensional multilayer material. Its single layer is composed of a [XO] (X is a metal element) atomic plane sandwiching a halogen (Cl-) ion layer to form a sandwich-type unit layer. The unit layer is stably connected by a strong ion-covalent bond network, and the layers are connected by van der Waals forces to form a multilayer material.

[0033] As a preferred technical solution of the present invention, the thickness of the chlorine oxide gate dielectric material is 5nm to 50nm, such as 5nm, 10nm, 15nm, 20nm, 25nm, 30nm, 35nm, 40nm, 45nm or 50nm.

[0034] Preferably, the dielectric constant of the oxychloride gate dielectric material is ≥30, such as 30, 32, 35, 38 or 40.

[0035] Preferably, the average surface roughness Ra of the oxychloride gate dielectric material is less than 0.2 nm, such as 0.19 nm, 0.18 nm, 0.17 nm, 0.16 nm, 0.15 nm, 0.14 nm, 0.13 nm, 0.12 nm or 0.11 nm.

[0036] Thirdly, the present invention also provides an application of a chlorine oxide gate dielectric material, wherein the chlorine oxide gate dielectric material prepared by the preparation method described in the first aspect, or the chlorine oxide gate dielectric material described in the second aspect, is applied to transistor devices and / or capacitor devices.

[0037] Compared with the prior art, the present invention has at least the following beneficial effects:

[0038] (1) This invention prepares high-quality chlorine oxide gate dielectric materials with controllable and uniform morphology by precisely controlling the condition parameters in the chemical vapor deposition process, which effectively solves the problem of random growth shape of chlorine oxide gate dielectric materials in the chemical vapor deposition process.

[0039] (2) By controlling the relative humidity of the reaction chamber during the chemical vapor deposition process, the present invention can control the ratio between different shapes (quadrilaterals and octagons) in the obtained oxychloride gate dielectric material, and achieves the controllable growth of high dielectric constant oxychloride gate dielectric material. In addition, it has an atomically flat surface. When applied to transistor devices and / or capacitor devices, the devices will have higher performance.

[0040] (3) The transistor device fabricated based on oxychloride gate dielectric material of the present invention has a high dielectric constant and excellent electrical performance, such as low off-state current, low gate leakage current, high on / off ratio, and subthreshold swing close to the room temperature limit. It effectively avoids short-channel effect and improves the performance stability and reliability of transistor. Specifically, the channel current on / off ratio of the transistor is ≥1×10 4 Gate leakage current ≤1×10 -12 A, Subthreshold swing ≤ 70mV dec -1 It has broad application prospects in the semiconductor field. Attached Figure Description

[0041] Figure 1 This is a schematic diagram of the preparation of the BiOCl gate dielectric material provided in Embodiment 1 of the present invention.

[0042] Figure 2 This is an optical photograph of the octagonal BiOCl gate dielectric material provided in Embodiment 1 of the present invention.

[0043] Figure 3 This is an optical photograph of the quadrilateral BiOCl gate dielectric material provided in Embodiment 1 of the present invention.

[0044] Figure 4 This is an XRD pattern of the BiOCl gate dielectric material provided in Embodiment 1 of the present invention.

[0045] Figure 5 This is the Raman spectrum of the BiOCl gate dielectric material provided in Embodiment 1 of the present invention.

[0046] Figure 6 This is an optical photograph of the BiOCl gate dielectric material provided in Embodiment 3 of the present invention.

[0047] Figure 7 This is an optical photograph of the BiOCl gate dielectric material provided in Embodiment 4 of the present invention.

[0048] Figure 8 This is a schematic diagram of the field-effect transistor structure provided in Application Example 1 of the present invention.

[0049] Figure 9 This is a schematic diagram of the capacitor device structure provided in Application Example 5 of the present invention.

[0050] Figure 10 This is a capacitance / voltage measurement diagram of the capacitor device provided in Application Example 5 of the present invention at different frequencies.

[0051] Among them, 1-BiOCl gate dielectric material, 2-bismuth chloride, 3-argon / hydrogen mixture, 4-hygroscopic silica gel, 5-water vapor, 6-top gate electrode, 7-molybdenum disulfide, 8-Si / SiO2 substrate, 9-top electrode, 10-bottom electrode, and 11-AC power supply. Detailed Implementation

[0052] The technical solution of the present invention will be further described below with reference to the accompanying drawings and specific embodiments. However, the following examples are merely simplified examples of the present invention and do not represent or limit the scope of protection of the present invention. The scope of protection of the present invention is determined by the claims.

[0053] Unless otherwise stated, the raw materials and reagents used in the following examples are commercially available products or can be prepared by known methods.

[0054] Example 1

[0055] This embodiment provides a method for preparing a chloride oxide gate dielectric material. Figure 1 This diagram illustrates the fabrication process of the BiOCl gate dielectric material provided in Embodiment 1 of the present invention. The fabrication method includes the following steps:

[0056] Bismuth chloride (BiCl3)2 was placed at the bottom of a single-opening test tube, and freshly pyrolyzed fluorocrystalline mica was placed at the opening of the test tube. The tube was then placed in a CVD tube furnace with the opening facing the vent, ensuring the bismuth chloride was centered within the furnace chamber. Moisture-absorbing silica gel 4 was placed at the vent to maintain relative humidity within the reaction chamber. Before deposition, an argon / hydrogen mixture 3 (300 sccm / 10 min) was introduced to remove excess gas from the furnace (reaction chamber). Then, another argon / hydrogen mixture was introduced as a carrier gas (50 sccm) to carry the water vapor 5 naturally released by the silica gel. The relative humidity of the reaction chamber was controlled to 11.4%, and deposition was performed at 500℃ for 20 min to obtain a 30 nm thick nanosheet BiOCl gate dielectric material 1.

[0057] Figure 2 An optical photograph of the octagonal BiOCl gate dielectric material provided in Embodiment 1 of the present invention is shown. Figure 3 An optical photograph of the quadrilateral BiOCl gate dielectric material provided in Embodiment 1 of the present invention is shown. As can be seen from the figure, the BiOCl gate dielectric material has a uniform morphology and is a two-dimensional nanosheet morphology.

[0058] The BiOCl gate dielectric material provided in Example 1 was characterized by XRD using a powder X-ray diffractometer (Bruker AXS D8 ADVANCE instrument, Germany) and Raman spectroscopy was performed using a Renishaw InviaQontor instrument at a laser wavelength of 532 nm. Figure 4 The XRD pattern of the BiOCl gate dielectric material provided in Embodiment 1 of the present invention is shown. Figure 5 The Raman spectrum of the BiOCl gate dielectric material provided in Embodiment 1 of the present invention is shown. As can be seen from the figure, the obtained gate dielectric material is BiOCl, and the characteristic peak of the Raman spectrum is located at 145 cm⁻¹. -1 The (001) diffraction peak in the XRD pattern confirms a single-crystal structure. Figure 4 The Mica in the figure corresponds to the characteristic peak of fluorinated mica.

[0059] The surface morphology of the BiOCl gate dielectric material provided in Example 1 was monitored using an atomic force microscope (Bruker Dimension ICON). The average surface roughness Ra of the BiOCl gate dielectric material measured in tapping mode was <0.2 nm.

[0060] Example 2

[0061] This embodiment provides a method for preparing a chloride oxide gate dielectric material. The difference between this method and Example 1 is that the relative humidity of the reaction chamber is controlled at 16.6%, while the rest of the preparation method and parameters are the same as in Example 1.

[0062] Example 3

[0063] This embodiment provides a method for preparing a chloride oxide gate dielectric material. The difference between this method and Example 1 is that the relative humidity of the reaction chamber is controlled to be 8.7%, while the rest of the preparation method and parameters are the same as in Example 1.

[0064] Figure 6 An optical photograph of the BiOCl gate dielectric material provided in Embodiment 3 of the present invention is shown. As can be seen from the figure, octagonal BiOCl gate dielectric material is relatively abundant and accounts for a high proportion.

[0065] Example 4

[0066] This embodiment provides a method for preparing a chloride oxide gate dielectric material. The difference between this method and Example 1 is that the relative humidity of the reaction chamber is controlled at 19.5%, while the rest of the preparation method and parameters remain the same as in Example 1.

[0067] Figure 7An optical photograph of the BiOCl gate dielectric material provided in Embodiment 4 of the present invention is shown. As can be seen from the figure, quadrilateral BiOCl gate dielectric material is relatively more abundant and accounts for a higher proportion.

[0068] Example 5

[0069] This embodiment provides a method for preparing a chloride oxide gate dielectric material. The difference between this method and Example 1 is that the relative humidity of the reaction chamber is controlled at 6%, while the rest of the preparation method and parameters remain the same as in Example 1.

[0070] In this embodiment 5, BiOCl with controllable and uniform morphology cannot be obtained and therefore cannot be applied to devices.

[0071] Example 6

[0072] This embodiment provides a method for preparing a chloride oxide gate dielectric material. The difference between this method and Example 1 is that the relative humidity of the reaction chamber is controlled at 22%, while the rest of the preparation method and parameters remain the same as in Example 1.

[0073] In this embodiment 6, BiOCl with controllable and uniform morphology cannot be obtained, and therefore cannot be applied to devices.

[0074] Example 7

[0075] This embodiment provides a method for preparing a chloride oxide gate dielectric material. The difference between this method and Example 1 is that the deposition temperature is 400°C, while the rest of the preparation method and parameters are the same as in Example 1.

[0076] Example 8

[0077] This embodiment provides a method for preparing a chloride oxide gate dielectric material. The difference between this method and Example 1 is that the deposition temperature is 450°C, while the rest of the preparation method and parameters are the same as in Example 1.

[0078] Example 9

[0079] This embodiment provides a method for preparing a chloride oxide gate dielectric material. The difference between this method and Example 1 is that the deposition temperature is 480°C, while the rest of the preparation method and parameters are the same as in Example 1.

[0080] Example 10

[0081] This embodiment provides a method for preparing a chloride oxide gate dielectric material. The difference between this method and Example 1 is that the deposition temperature is 540°C, while the rest of the preparation method and parameters are the same as in Example 1.

[0082] In this embodiment 10, the deposition temperature was too high, which caused the internal crystal structure of the BiOCl gate dielectric material to be destroyed, so it could not be applied to the device.

[0083] Example 11

[0084] This embodiment provides a method for preparing a chloride oxide gate dielectric material. The difference between this method and Example 1 is that the deposition temperature is 380°C, while the rest of the preparation method and parameters are the same as in Example 1.

[0085] In this embodiment 11, the deposition temperature is too low, so the nucleation temperature cannot be reached. The chlorine oxide gate dielectric material obtained on the substrate surface has poor crystallinity and excessive leakage current, so it cannot be applied to the device.

[0086] Comparative Example 1

[0087] This comparative example provides a method for preparing a chloride oxide gate dielectric material. The difference between this preparation method and Example 1 is that bismuth chloride (BiCl3) is placed at the mouth of a single-opening test tube, and freshly pyrolyzed fluorinated mica is placed at the bottom of the mouth of the single-opening test tube as a substrate. Then, the tube is placed in a CVD tube furnace with the opening facing the vent, and the bismuth chloride is ensured to be located in the center of the tube furnace chamber. The rest of the preparation method and parameters are the same as in Example 1.

[0088] The nanosheet gate dielectric materials provided in Examples 1-4 were subjected to the following tests:

[0089] (1) The proportion of gate dielectric materials of different shapes was observed by optical microscope (RX50M microscope).

[0090] (2) The dielectric constant is calculated using the formula ε=C*d / ε0*A, where C is the measurement capacitance, A is the overlapping area of ​​the electrodes, d is the sample thickness, and ε0 is the vacuum dielectric constant.

[0091] Table 1

[0092]

[0093] The test results in Table 1 show that:

[0094] (1) As can be seen from Examples 1 to 4, the present invention combines chemical vapor deposition with relative humidity control. By controlling the relative humidity during the growth process, i.e., controlling the relative humidity of the reaction chamber to 8% to 20%, a morphology-controllable and uniform oxychloride gate dielectric material can be obtained, which has the characteristics of high-quality surface and high dielectric constant, and the dielectric constant is ≥30. In addition, as the relative humidity of the reaction chamber increases, the proportion of octagonal oxychloride gate dielectric material gradually decreases. The specific reason is that the octagonal oxychloride gate dielectric material has a more complex shape and more cut-off edges than the quadrilateral oxychloride gate dielectric material. The more cut-off edges, the higher the surface energy. After the surface energy is reduced by combining with water molecules, the product tends to grow towards the lower surface energy state with fewer cut-off edges. Therefore, as the relative humidity of the reaction chamber increases, the proportion of octagonal oxychloride gate dielectric material gradually decreases.

[0095] (2) As can be seen from Examples 1 and 5-6, by further controlling the relative humidity of the reaction chamber to 8%-20%, the present invention can achieve the preparation of morphology controllable and uniform oxychloride gate dielectric material, so that the oxychloride gate dielectric material nanosheets tend to grow into octagonal or quadrilateral shapes, with more uniform morphology, that is, uniform thickness, uniform size and high surface flatness. When applied to devices, it has a significant positive effect on improving performance.

[0096] (3) As can be seen from Example 1 and Comparative Example 1, the present invention places the chloride precursor at the bottom of the single-sided open reaction vessel and the substrate material at the single-sided open reaction vessel. During the deposition process, the chloride precursor evaporates into molecules and remains in the reaction vessel, ensuring that the reaction vessel is always filled with a high concentration of precursor gas molecules. This allows for better deposition of high-quality chloride oxide gate dielectric material on the substrate surface. However, if the positions of the two are interchanged, i.e., the chloride precursor is placed at the single-sided open reaction vessel and the substrate material is placed at the bottom of the single-sided open reaction vessel, it is impossible to ensure that the entire reaction vessel is filled with a high concentration of precursor gas molecules. The presence of the carrier gas will cause the precursor gas molecules to be blown away, thus making it impossible to prepare a BiOCl gate dielectric material with controllable and uniform morphology.

[0097] Application Example 1

[0098] This application example provides a transistor device in which the BiOCl gate dielectric material prepared in Example 1 is separated from fluorocrystalline mica using a wet transfer method. The method includes: spin-coating a PMMA A4 solution of a certain concentration onto the surface of the fluorocrystalline mica on which the BiOCl gate dielectric material is grown using a spin coater, setting a stepped spin-coating program—the first stage at 500 rpm / 5s to achieve solution spreading, and the second stage at 2000 rpm / 60s to form a polymer support layer of uniform thickness; then placing the sample covered with PMMA on a hot plate and baking it at 150°C for 1 min to allow the solvent to evaporate completely and form a dense protective film; next, flatly attaching a PDMS elastomer to the PMMA surface, applying a pressure of 0.5 MPa and holding it for 30s to ensure bubble-free interface bonding; then vertically immersing the composite structure in deionized water, utilizing the different hydrophilicity of fluorocrystalline mica and BiOCl gate dielectric material, selective separation of the fluorocrystalline mica / BiOCl gate dielectric material interface is achieved after 3 hours of gentle immersion; the separated BiOCl / PMMA / PDMS composite structure is dried with nitrogen gas for later use.

[0099] A Si / SiO2 substrate 8 is provided. A BiOCl / PMMA composite structure is precisely stacked on top of a mechanically peeled molybdenum disulfide (MoS2) 7 channel layer using a two-dimensional material transfer stage. The two structures are bonded together by van der Waals forces to form a heterojunction. The heterojunction and substrate are immersed in acetone solution for 30 minutes to remove excess PMMA, retaining the BiOCl gate dielectric material 1. A 7nm Cr adhesion layer and a 73nm Au layer are fabricated using electron beam lithography and evaporation to form the top gate electrode 6, resulting in field-effect transistors (FETs). A schematic diagram is shown below. Figure 8 As shown.

[0100] Application Example 2

[0101] This application example provides a transistor device that uses the BiOCl gate dielectric material provided in Example 7, while the rest of the fabrication methods and parameters are consistent with those in Application Example 1.

[0102] Application Example 3

[0103] This application example provides a transistor device that uses the BiOCl gate dielectric material provided in Example 8, while the remaining fabrication methods and parameters are consistent with those in Application Example 1.

[0104] Application Example 4

[0105] This application example provides a transistor device that uses the BiOCl gate dielectric material provided in Example 9, while the remaining fabrication methods and parameters are consistent with those in Application Example 1.

[0106] The field-effect transistors provided in Application Examples 1-4 are respectively subjected to 10... -3Under vacuum conditions, the channel current on / off ratio, gate leakage current, and subthreshold swing were tested using a Keithley 4200A-SCS semiconductor parameter analyzer at a drain-source voltage (VDS) of 500mV. The specific test results are shown in Table 2.

[0107] Table 2

[0108] project Channel current on / off ratio Gate leakage current (A) <![CDATA[Subthreshold swing (mV / dec -1 )]]> Application Example 1 <![CDATA[1.0×10 7 ]]> <![CDATA[1.0×10 -15 ]]> 66.7 Application Example 2 <![CDATA[1.0×10 4 ]]> <![CDATA[1.0×10 -12 ]]> 62 Application Example 3 <![CDATA[1.0×10 6 ]]> <![CDATA[1.0×10 -14 ]]> 65 Application Example 4 <![CDATA[1.0×10 6 ]]> <![CDATA[1.0×10 -14 ]]> 69

[0109] The test results in Table 2 show that:

[0110] In Application Examples 1-4, the transistor devices fabricated from the BiOCl gate dielectric material provided by this invention all exhibit high performance, with a channel current on / off ratio ≥ 1 × 10⁻⁶. 4 Gate leakage current ≤1×10 -12 A, Subthreshold swing ≤ 70mV dec -1 This also indicates that the BiOCl gate dielectric material with uniform and controllable morphology provided in the above embodiments of the present invention has a high dielectric constant and superior performance.

[0111] Application Example 5

[0112] This application example provides a capacitor device in which the BiOCl gate dielectric material prepared in Example 1 is separated from fluorinated mica by a wet transfer method, and the separation method is consistent with that in Application Example 1.

[0113] Using Si / SiO2 as a substrate, a 5nm Cr adhesion layer and a 15nm Au layer are first deposited on the substrate via evaporation to form the bottom electrode 10. A BiOCl / PMMA composite structure is then precisely stacked on top of the bottom electrode using a two-dimensional material transfer stage. Excess PMMA is removed by immersion in acetone for at least 30 minutes. Next, a 7nm Cr adhesion layer and a 73nm Au layer are deposited on top of the BiOCl gate dielectric material 1 via evaporation to form the top electrode 9. An AC power supply 11 is then connected to obtain the capacitor device. A schematic diagram is shown below. Figure 9 As shown.

[0114] In 10 -3 Under vacuum conditions, the capacitance values ​​of the BiOCl gate dielectric material at different frequencies were tested using a Keithley 4200A-SCS semiconductor parameter analyzer. Figure 10 The figure shows the capacitance / voltage measurement graphs of the capacitor device provided in Application Example 5 of the present invention at different frequencies. As can be seen from the figure, the change in capacitance of the BiOCl gate dielectric material at different frequencies is negligible, indicating that it is a stable dielectric material.

[0115] In summary, this invention utilizes chemical vapor deposition (CVD) to control the preparation process and obtain morphology-controllable and uniform oxychloride gate dielectric materials, thus solving the problems of random shape and uneven morphology of oxychloride gate dielectric materials during CVD. This enables controllable growth of the material with a high dielectric constant. Furthermore, it possesses an atomically flat surface, which, when applied to transistor devices and / or capacitor devices, will result in higher performance.

[0116] The applicant declares that the above description is only a specific embodiment of the present invention, but the protection scope of the present invention is not limited thereto. Those skilled in the art should understand that any changes or substitutions that can be easily conceived by those skilled in the art within the technical scope disclosed in the present invention fall within the protection and disclosure scope of the present invention.

Claims

1. A method for preparing a chloride oxide gate dielectric material, characterized in that, The preparation method includes the following steps: A chloride precursor and a substrate material are placed at the bottom and a single-sided opening of the same reaction vessel. The single-sided opening reaction vessel is placed in a chemical vapor deposition apparatus with its opening facing the vent of the vapor deposition apparatus. A chloride oxide gate dielectric material is deposited on the surface of the substrate material.

2. The preparation method according to claim 1, characterized in that, During the deposition process, the relative humidity in the reaction chamber is 8% to 20%.

3. The preparation method according to claim 2, characterized in that, The method for achieving relative humidity in the reaction chamber using hygroscopic silica gel includes: The dried silica gel is soaked in deionized water until it is saturated with moisture to obtain hygroscopic silica gel. The hygroscopic silica gel is placed between the vent and the opening of the single-sided open reaction vessel. The hygroscopic silica gel releases water vapor, so that the reaction chamber has relative humidity.

4. The preparation method according to any one of claims 1 to 3, characterized in that, The deposition time is 10 min to 30 min; Preferably, the deposition temperature is 400℃~500℃.

5. The preparation method according to any one of claims 1 to 4, characterized in that, The carrier gas supplied by the vent includes an argon / hydrogen mixture; Preferably, the air vent provides a carrier gas flow rate of 50 sccm to 100 sccm.

6. The preparation method according to any one of claims 1 to 5, characterized in that, The chloride precursor includes any one or a combination of at least two of BiCl3, GdCl3, or VCl3; Preferably, the substrate material includes any one of mica substrate, Si substrate, SiO2 substrate or sapphire substrate.

7. A chloride oxide gate dielectric material, characterized in that, The chlorine oxide gate dielectric material is prepared by the preparation method according to any one of claims 1 to 6.

8. The oxychloride gate dielectric material according to claim 7, characterized in that, The chlorine oxide gate dielectric material is a two-dimensional multilayer material.

9. The oxychloride gate dielectric material according to claim 7 or 8, characterized in that, The thickness of the chlorine oxide gate dielectric material is 5 nm to 50 nm. Preferably, the dielectric constant of the oxychloride gate dielectric material is ≥30.

10. An application of a chloride oxide gate dielectric material, characterized in that, The oxychloride gate dielectric material prepared by the preparation method according to any one of claims 1 to 6, or the oxychloride gate dielectric material according to any one of claims 7 to 9, is applied to transistor devices and / or capacitor devices.

Citation Information

Cited By

  • Method for growing p-type two-dimensional semiconductor film in selected area at low temperature and preparation of transistor

    CN121888874A

  • Method for low-temperature selective growth of p-type two-dimensional semiconductor thin film and preparation of transistor

    CN121888874B